Agricultural Extension: Challenges of Extension service for rural poor and youth in Amhara Region, North Western Ethiopia. The Case of North Gondar Zone - Petros, Mrs.Tigist; Nachimuthu, Dr.Kavitha; Atinikut, Mr. Haimanot; Mohammed, Mr. (International Journal of Scientific Research and Management (IJSRM), 2018)
Ethiopia is one of the countries on the African continent with highest agricultural potential. Its natural resources base is the foundation of any economic development, food security and other basic necessities of its people. Predominantly smallholder agriculture is the dominant sector of the national economy. Smallholder agriculture is the dominant sector of the national economy. To boost the production and productivity of the agriculture sector; the extension systems is expected to play paramount role. However, the agricultural system is still characterized by low level of Agricultural service delivery practice that couldn’t move the existing traditional agriculture in to modern. The objective of the study is toexamine constraints in addressing women farmers and rural youth and to assess constraints of extension system  in promoting agricultural technologies to farmers in the study area. Primary and Secondary data was collected for the study purpose. In addition to respondents’ interview, focus group discussion, key informants interview and case studies were used for qualitative data analysis. Descriptive statistics of mean, standard devotions and percent was applied. For statistical tests, chi-square, T-test, Pearson and spearman’s correlation coefficient were employed. As a conclusion, the challenges of existing public agricultural extension service provision institutional, technological and technical and in terms of addressing cross-cutting issues such as environment and gender as theses have wider contexts to look into existing endogenous and exogenous constraints.